Freshwater crabs of the genus Phallangothelphusa Preztmann, 1965 from Colombia (Malacostraca: Decapoda: Pseudothelphusidae): Description of a new species and an updated key to the species - Campos, Martha R.; Alexander, Moises (Zootaxa, 2026)
A new species of Phallangothelphusa Pretzmann, 1965, is described from El Bagre Municipality, Antioquia Department, Colombia, increasing the known diversity of the genus to seven species. The other six recognized species are P. dispar (Zimmer, 1912), P. magdalenensis Campos, 1998, P. juansei Campos, 2010, P. martensis Cardona & Campos, 2012, P. tangerina Campos, Lasso & Arias, 2019, P. zenuorum Campos & Alexander, 2020. The new species is distinguished from its congeners primarily by the relative length of the exopod of the third maxilliped and the morphology of the first and second male gonopods. Specifically, diagnostic features of the first male gonopod include the apex outline and the shapes of the mesial and lateral processes, while the second gonopod is characterized by the shape of the endopodite and its distal portion. An updated identification key for all Phallangothelphusa species is provided.